The Cacna1h mutation in the GAERS model of absence epilepsy enhances T-type Ca2+ currents by altering calnexin-dependent trafficking of Cav3.2 channels - Proft, Juliane; Rzhepetskyy, Yuriy; Lazniewska, Joanna; Zhang, Fang-Xiong; Cain, Stuart M; Snutch, Terrance P; Zamponi, Gerald W; Weiss, Norbert (Scientific reports, 2017)
Low-voltage-activated T-type calcium channels are essential contributors to the functioning of thalamocortical neurons by supporting burst-firing mode of action potentials. Enhanced T-type calcium conductance has been reported in the Genetic Absence Epilepsy Rat from Strasbourg (GAERS) and proposed to be causally related to the overall development of absence seizure activity. Here, we show that calnexin, an endoplasmic reticulum integral membrane protein, interacts with the III-IV linker region of the Cav3.2 channel to modulate the sorting of the channel to the cell surface. We demonstrate that the GAERS missense mutation located in the Cav3.2 III-IV linker alters the Cav3.2/calnexin interaction, resulting in an increased surface expression of the channel and a concomitant elevation in calcium influx. Our study reveals a novel mechanism that controls the expression of T-type channels, and provides a molecular explanation for the enhancement of T-type calcium conductance in GAERS.
Keywords: mutantní proteiny; Calcium Channels, T-Type; Protein Transport; Mutant Proteins; krysa rodu Rattus; vápníkové kanály - typ T; absentní epilepsie; Animals; Disease Models, Animal; kalnexin; Epilepsy, Absence; modely nemocí na zvířatech; missense mutace; zvířata; transport proteinů; Rats; Calnexin; Mutation, Missense